Recurrent appendicitis following successful drainage of appendicular abscess in adult without interval appendectomy during COVID-19. Prospective cohort study. (January 2022) - Habeeb, Tamer A.A.M.; Hussain, Abdulzahra; Schlottmann, Francisco; Kermansaravi, Mohammad; Aiolfi, Alberto; Matic, Ivan; Abdelazez, Osama; negm, Said mohamed; Baghdadi, Muhammad Ali; Abdou yassin, Mahmoud; Sallam, Ahmed M.; Mohammad, Hatem; et al.
Abstract: Background: COVID-19 infection is a global pandemic that affected routine health services and made patients fear to consult for medical health problems, even acute abdominal pain. Subsequently, the incidence of complicated appendicitis increased during the Covid-19 pandemic. This study aimed to evaluate recurrent appendicitis after successful drainage of appendicular abscess during COVID-19. Material and methods: A prospective cohort study conducted in the surgical emergency units of our Universities' Hospitals between March 15, 2020 to August 15, 2020 including patients who were admitted with the diagnosis of an appendicular abscess and who underwent open or radiological drainage. Main outcomes included incidence, severity, and risk factors of recurrent appendicitis in patients without interval appendectomy. Results: A total of 316 patients were included for analysis. The mean age of the patients was 37 years (SD ± 13). About two-thirds of patients were males (60.1%). More than one-third (39.6%) had co-morbidities; type 2 diabetes mellitus (T2DM) (22.5%) and hypertension (17.1%) were the most frequent. Approximately one quarter (25.6%) had confirmed COVID 19 infection. About one-third of the patients (30.4%) had recurrent appendicitis. More than half of them (56.3%) showed recurrence after three months, and 43.8% of patients showed recurrence in the first three months. The most frequent grade was grade I (63.5%). Most patients (77.1%) underwent open surgery. Age, T2DM, hypertension, COVID-19 infection and abscess size >3 cm were significantly risking predictors for recurrent appendicitis. Conclusions: Interval appendectomy is suggested to prevent 56.3% of recurrent appendicitis that occurs after 3 months. We recommend performing interval appendectomy in older age, people with diabetes, COVID-19 infected, and abscesses more than 3 cm in diameter. Research question: Is interval appendectomy preventing a high incidence of recurrent appendicitis after successful drainage of appendicular abscess during COVID-19 pandemic? Highlights: About 1/3 of patients (30.4%) had recurrent appendicitis after successful drainage of AA (43.7% after three months). The most frequent grade of severity of recurrent appendicitis was grade I (63.5%). Older age, T2DM, abscess size > 3cm, and COVID-19 infections were independent risk factors for recurrent appendicitis.